1996
DOI: 10.1101/gad.10.22.2849
|View full text |Cite
|
Sign up to set email alerts
|

TrkB and TrkC neurotrophin receptors cooperate in promoting survival of hippocampal and cerebellar granule neurons.

Abstract: The Trk family of protein tyrosine kinases (TrkA/B/C) are receptors for neurotrophins, a family of closely related proteins that are important physiological regulators of the survival of specific neurons within the peripheral nervous system (PNS) of vertebrates. In contrast to the PNS, brains of mutant mice deficient in a single neurotrophin or Trk receptor species do not show signs of major cell loss. However, in double mutant mice, we now show that reducing the expression of both TrkB and TrkC causes massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
166
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(187 citation statements)
references
References 54 publications
21
166
0
Order By: Relevance
“…Previous work has shown that BDNF does not promote survival of embryonic rat hippocampal pyramidal neurons in culture Marsh and Palfrey, 1996). Previous work has also indicated that there is not a requirement for BDNF or TrkB for survival of neonatal hippocampal pyramidal neurons in vivo (Jones et al, 1994;Minichiello and Klein, 1996;Alcántara et al, 1997). Results in the present paper extend this work by providing evidence that TrkB is not required for survival of CA1 pyramidal neurons in the mature brain.…”
Section: Survival and Dendritic Differentiation Of Ca1 Pyramidal Neursupporting
confidence: 80%
See 1 more Smart Citation
“…Previous work has shown that BDNF does not promote survival of embryonic rat hippocampal pyramidal neurons in culture Marsh and Palfrey, 1996). Previous work has also indicated that there is not a requirement for BDNF or TrkB for survival of neonatal hippocampal pyramidal neurons in vivo (Jones et al, 1994;Minichiello and Klein, 1996;Alcántara et al, 1997). Results in the present paper extend this work by providing evidence that TrkB is not required for survival of CA1 pyramidal neurons in the mature brain.…”
Section: Survival and Dendritic Differentiation Of Ca1 Pyramidal Neursupporting
confidence: 80%
“…Despite this, comparatively few deficits have been seen in the brains of mice lacking individual neurotrophins or Trk receptors (for review, see Reichardt and Fariñas, 1997). In the hippocampus, the deficits observed include a small increase postnatally in granule cell apoptosis and striking reductions in expression of calbindin, parvalbumin, and neuropeptide Y in GABAergic interneurons (Jones et al, 1994;Minichiello and Klein, 1996;Alcántara et al, 1997). Except for the NT-4 mutant, all of the neurotrophin-and Trk-deficient mice have quite limited postnatal life spans, seldom surviving beyond a couple of weeks.…”
Section: Abstract: Trkb; Conditional Mutant; Ca1; Long-term Potentiamentioning
confidence: 99%
“…It has been reported that NeuroD is an upstream regulator of neurotrophin receptors in the differentiating neurons of inner ear (Kim et al, 2001). In the cerebellum, Trk/neurotrophin signaling is essential for the migration, polarization, and survival of the cerebellar granule cells (Borghesani et al, 2002;Lindholm et al, 1996;Minichiello and Klein, 1996). In the hippocampus, TrkB and TrkC signaling cooperate to promote the survival of the DG granular neurons (Minichiello and Klein, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebellum, Trk/neurotrophin signaling is essential for the migration, polarization, and survival of the cerebellar granule cells (Borghesani et al, 2002;Lindholm et al, 1996;Minichiello and Klein, 1996). In the hippocampus, TrkB and TrkC signaling cooperate to promote the survival of the DG granular neurons (Minichiello and Klein, 1996). The signaling of TrkB and its major ligand, BDNF (brain-derived neurotrophic factor), is particularly important for the development of vestibular ganglion neurons, while signaling through TrkC and its high affinity ligand NT-3 (neurotrophin-3) is primarily required for the survival and innervations of the acoustic ganglia (Wheeler et al, 1994;Ylikoski et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were studied which had had the trkB gene knocked-out in the forebrain during postnatal development. The mice developed without gross morphological defects (the mice do not survive until adulthood if the gene is knocked-out for the entire brain [72]), and the activity of the trkB-mice in an open field were similar to wild-type mice. However, in a Morris water maze experiment (similar to that of Case study 1), although the control mice learnt the route to the hidden platform (left track in Fig.…”
Section: 4mentioning
confidence: 99%